Public Private Partnership (PPP) and its Evolution – A Conceptual Framework (International Journal of Scientific Research and Management (IJSRM), 2017)
India’s economy has experienced rapid progression since the attempt of liberalization in 1991. To keep pace with this growth, physical infrastructure such as transportation systems, communication systems, energy systems, water and sanitation networks etc need to be developed. The burgeoning investments required have necessitated the government to look for ways and means to scale up the infrastructure. Typically the governments have been using – Engineering, Procurement and Construction (EPC) method for infrastructure provisioning. The constraints on the availability of finance on one side and the need to provide social good on the other side has had its impact not only on the performance of existing but also on the addition of new infrastructure. To cope up with this dilemma and to increase the share of private sector in country’s infrastructure development, the government initiated Public Private Partnership. PPP is a contractual agreement between the public sector and private sector partners for a pre-defined period. This arrangement allows the government to have access to the financial resources, technical & managerial experience, expertise and efficiency of the private sector and share most of the risks in providing specified infrastructure services. The success of PPP relies on designing viable projects, minimizing speculation on uncontrollable factors, having fair and transparent procurement process & a competitive environment and an efficient financially system.